Bit Error Rate (BER) QoS Attribute in Solving Wireless Pricing Scheme on Single Link Multi Service Network - Irmeilyana Irmeilyana; Fitri Maya Puspita; Indrawati Indrawati; Rahayu Tamy Agustin (Institute of Advanced Engineering and Science, 2018)
Pricing schemes were set up on multi service network of wireless internet pricing scheme to proposed models applying Bit Error Rate QoS attribute due to requirements for ISP to maximize revenue and provide high quality of service to end users.The model was deigned by improving the original model together with added parameters and variables to the model of multi- service network by setting the base price (α) and premium quality (β) as variables and parameters. LINGO 11.0 were applied to help finding the solution. The results show that the improved models yield maximum revenue for ISP by applying the improved model by setting up a variable α and β as constant as well as by increasing the cost of all the changes in QoS. The QoS attriute BER is proven to achieve the ISP’s goal to maximize the revenue.